Улучшение качества жизни посредством оптимального использования сварочных технологий - Смаллбоне, К. (Автоматическая сварка, 2008)
This paper gives an overview of the work of IIW internationally, in various regions of the world and industry sectors utilising welding, the challenges being faced, opportunities available, and probable requirements for the successful introduction
and optimum use of welding technology. Successful models used in other countries, particularly for technology diffusion to industry, education and training, improving the image of welding and the use of appropriate technologies will be highlighted. The involvement of industry and governments across the world in conjunction with the work of IIW and
its 52 member countries, particularly the involvement of the Ukraine, is critical to the success of such initiatives.